Reduced reflectance and altered color: The potential cost of external particulate matter accumulation on urban Rock Pigeon (Columba livia) feathers - Ellis, Jennifer L.; Ponette-González, Alexandra G.; Fry, Matthew; Johnson, Jeff A. (Frontiers in Ecology and Evolution, 2023)
Feather quality in birds is considered an honest signal of individual health as feather appearance and function depend on an individual’s ability to maintain them. In addition to flight and insulation, feathers are essential for social interactions and sexual selection in the form of visual signals. Airborne particulate matter (PM) can accumulate on feather surfaces and alter feather appearance. We quantified PM accumulation on Rock Pigeon (Columba livia) feathers and analyzed the spectral properties of extracted particulates. Feathers were sampled from two pigeon populations, one rural and one urban, in the Dallas-Fort Worth area, with 47% and 93% developed land cover, respectively, within 2 km of the populations. We determined accumulated PM gravimetrically after rinsing feathers and then measured the visible-near-infrared diffuse reflectance and color properties of extracted particulates. The rate of PM accumulation on rural birds was higher than on urban birds. However, feather particulates collected from urban pigeons had significantly lower total reflectance, reflectance in the visible portion of the spectrum, lightness, and hue angle compared to those of rural pigeons. The hue angle of rural feather particulates displayed a negative relationship with PM accumulation while total reflectance, reflectance in the visible range, and lightness of urban feather particulates were negatively related to PM accumulation. Our findings suggest that wild birds could incur an urban pollution penalty as PM accumulation has the potential to alter feather properties. Further research is needed to better understand the influence of external PM accumulation on the physiological and behavioral health of birds.